PENGARUH UKURAN PARTIKEL LIMBAH KOPI TERHADAP KARAKTERISASI SIFAT MEKANIK PADA PANEL KOMPOSIT - Haidzar Nurdiansyah; Sumarji Sumarji; Ahmad Syuhri; Dedi Dwi Laksana; Muhammad Abduh (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2017)
Panel composite materials using filler coffee waste particles with various particle sizes have been analyzed for effect. The matrix used is 2504APT eterset polyester resin, and the method used in making composites is the vacuum method. Particle size variations used are using mesh sizes 30, 40, 50, 60, and 70. Mechanical strengths such as tensile strength and bending strength are compared and evaluated. Interface analysis was also carried out by using a micro-test to determine the microstructure of the test specimens. The tensile strength obtained by the most significant value on the 50 mesh is 24.89 MPa, while the highest bending strength value is in the 60 mesh of 50.9 MPa. The addition of coffee waste particles with various sizes influences the mechanical properties of the coffee waste composite panel. Keywords: panel composites, coffee waste particles, particle size, mechanical properties, microstructure